The Correlation Between EFL Learners' Metacognitive Awareness and Listening Comprehension - Pancarwati, Mahar Ayu (RETAIN, 2021)
Abstract Having metacognitive awareness is essentially needed to assist the individual learner in accomplishing listening performance better. Only several studies which investigated carefully on the relationship between metacognitive awareness strategies and students’ listening comprehension achievement in Indonesia context. The previous studies also did not specifically examine on the students’ metacognitive awareness in accomplishing the listening test. Thus, this quantitative study aims to examine the metacognitive awareness listening strategies applied by EFL learners in the listening comprehension test and also to find out its correlation. The data were obtained from online questionnaire with the total sample of 66 including the sophomore and junior university students in one of universities in Surabaya. Based on the research data analysis, students mostly apply problem-solving strategies with the means score 4.89 then it was followed by planning and evaluation with means score 4.50, direct attention with means score 4.43, mental translation with means score 3.95, and the least used was person knowledge with the means score 3.91. As for the results of the analysis of this study also revealed the correlation coefficient value r = -0.203 (P = 0.102; P> 0.05) which means there is no correlation between EFL Learners’ metacognitive awareness and listening comprehension score. Keywords: Listening Comprehension Score, Listening Comprehension Test, Metacognitive Awareness